Title Semiotic in Creative Texts (Journal of the College of Languages (JCL), 2018)
Contemporary researchers realized the importance of the title. Many researches and studies concerned in titles and their analyses on the structural, semantic and pragmatic levels have been developed. Title gives a vital assistance to control the text harmony and to understand its vague aspects. It is the axis which re-generates itself, grows, and re-produces itself; as if it were a head for a body.Title has strong relation to the reader- waiting horizon, multiplies as many levels of understanding are there. The horizon of waiting is limited by the title, basically, to be the first reason for the text entrance, as the first thing attracts the reader is the title.Approaching title scientifically and objectively is impossible, but only through semiotic approach which deals with titles being signs, signals, symbols, icons and metaphors.Under the light of these facts, semiotics dedicates vital importance for titles being procedural terms within the literary text approach.